2004
DOI: 10.1207/s15328015tlm1603_6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Retention of Knowledge After a Distance Course in Medical Informatics at Charles University Prague

Abstract: Retention of knowledge after the electronic distance course after 12 months is close to 67%. Other results indicate that we can expect better retention of knowledge from independent, responsible, and positively motivated students who can easily operate information technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Although, VTC is an expensive mode of teaching compared to other methods, the effectiveness of VTC training is far greater than other methods of distance education (Havice and Knowles 1995, Debourgh 2003, Nachinda 2003, Naidr et al 2004, Aslam and Waheed 2005.…”
Section: Video-teleconferencing (Vtc)mentioning
confidence: 99%
“…Although, VTC is an expensive mode of teaching compared to other methods, the effectiveness of VTC training is far greater than other methods of distance education (Havice and Knowles 1995, Debourgh 2003, Nachinda 2003, Naidr et al 2004, Aslam and Waheed 2005.…”
Section: Video-teleconferencing (Vtc)mentioning
confidence: 99%
“…While 2 weeks seem to be a short time, factors associated with short-and long-term knowledge retention are not well understood. 32,33 Contradictory to our hypothesis, we found that objective measures of academic performance (ie, examination scores) were diametrically opposed to students' own perceptions of how much they learned.…”
Section: Discussionmentioning
confidence: 67%
“…These dimensions are: affect, attitudes, intrinsic and extrinsic motivation . Research has also shown that positive attitudes and motivation toward online learning increases long term retention of knowledge significantly (Naidr et al, 2004).…”
Section: Dimensions Of Online Learningmentioning
confidence: 99%
“…Positive attitudes and motivation toward online learning has been shown to increase long term retention of knowledge significantly (Naidr et al, 2004). An ideal OLE makes use of affect, attitudes, intrinsic and extrinsic motivation to create a positive attitude in facilitators and learners.…”
Section: Intrinsic and Extrinsic Motivationmentioning
confidence: 99%